2019
DOI: 10.1111/jipb.12820
|View full text |Cite
|
Sign up to set email alerts
|

Tillering and small grain 1 dominates the tryptophan aminotransferase family required for local auxin biosynthesis in rice

Abstract: Auxin is a crucial phytohormone, controlling multiple aspects of plant growth and responses to the changing environment. However, the role of local auxin biosynthesis in specific developmental programs remains unknown in crops. This study characterized the rice tillering and small grain 1 (tsg1) mutant, which has more tillers but a smaller panicle and grain size resulting from a reduction in endogenous auxin. TSG1 encodes a tryptophan aminotransferase that is allelic to the FISH BONE (FIB) gene. The tsg1 mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Enhanced expression of Big Grain 1 (BG1), which is a positive regulator of auxin response and transport results in extra-large grains 48 . Moreover, plants with mutation in TILLERING AND SMALL GRAIN 1 (TSG1), which controls local auxin biosynthesis and affect auxin signaling and transport, exhibit small grains as a result of disruption of localized cell proliferation and cell expansion 36 . Consistent with these previous studies linking auxin to grain size, we found that GSA1 regulates grain size by finely modulating cell proliferation and cell expansion during different stages of spikelet development (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhanced expression of Big Grain 1 (BG1), which is a positive regulator of auxin response and transport results in extra-large grains 48 . Moreover, plants with mutation in TILLERING AND SMALL GRAIN 1 (TSG1), which controls local auxin biosynthesis and affect auxin signaling and transport, exhibit small grains as a result of disruption of localized cell proliferation and cell expansion 36 . Consistent with these previous studies linking auxin to grain size, we found that GSA1 regulates grain size by finely modulating cell proliferation and cell expansion during different stages of spikelet development (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2i). Interestingly, the expression level of TSG1, which controls grain size by regulating local auxin biosynthesis 36 , was significantly decreased in NIL-GSA1 CG14 ; the expression levels of the TSG1 homologs OsTAR1, OsTARL1, and OsTARL2 were also decreased ( Fig. 2i).…”
Section: Nil-gsa1 Cg14mentioning
confidence: 99%
See 1 more Smart Citation
“…The promotive effect of TAR and IAA for grain fill in wheat is supported by the positive effect on grain yield of TaTAR2.1-3A overexpression (Shao et al 2017). In addition, a mutant of the orthologous gene, tsg1, has a negative effect on grain size in rice (Guo et al 2019).…”
Section: Phylogenetic Analysis Of All Tar and Yucca Genes In Wheatmentioning
confidence: 96%
“…For example, the shrunken grain phenotype of defective endosperm and defective kernel mutants of maize, de18 and dek18 appears to result from low levels of IAA in the developing grains caused by mutations affecting ZmYUC1 expression (Bernardi et al 2012;Bernardi et al 2016). In rice, a mutation in the IAA biosynthesis gene OsTAR2/FIB is associated with the tillering and small grain 1 (tsg1) phenotype (Guo et al 2019). Finally, in wheat, Shao et al (2017) showed that overexpression of TaTAR2.1-3A…”
Section: Introductionmentioning
confidence: 99%